Phase I Trial of Carboplatin and Gemcitabine Chemotherapy and Stereotactic Ablative Radiosurgery for the Palliative Treatment of Persistent or Recurrent Gynecologic Cancer - Kunos, Charles A.; Sherertz, Tracy M.; Mislmani, Mazen; Ellis, Rodney J.; Lo, Simon S.; Waggoner, Steven E.; Zanotti, Kristine M.; Herrmann, Karin; Debernardo, Robert L. (Frontiers in Oncology, 2015)
Background: We conducted a phase I trial to determine the safety of systemic chemotherapy prior to abdominopelvic robotic stereotactic ablative radiotherapy (SABR) in women with persistent or recurrent gynecologic cancers. Methods: Patients were assigned to dose-finding cohorts of day-1 carboplatin (AUC 2 or 4) and gemcitabine (600 or 800 mg/m2) followed by day-2 to day-4 Cyberknife SABR (8Gy X 3 consecutive daily doses). Toxicities were graded prospectively by common terminology criteria for adverse events, version 4.0. SABR target and best overall treatment responses were recorded according to response evaluation criteria in solid tumors, version 1.1. Findings: The maximum tolerated dose of chemotherapy preceding SABR was carboplatin AUC 4 and gemcitabine 600 mg/m2. One patient experienced manageable, dose-limiting grade 4 neutropenia, grade 4 hypokalemia, and grade 3 nausea attributed to study treatment. One patient had a late grade 3 rectovaginal fistula 16 months after trial therapy. Among 28 SABR targets, 22 (79%) showed a partial response and six (21%) remained stable. Interpretation: Systemic chemotherapy may be given safely prior to abdominopelvic robotic SABR with further investigation warranted. Funding: National Institutes of Health grant P30 CA43703